Rethinking Accessibility in Light of the Orange Declaration: Applying a Socio-Ecological Lens to Rural Mental Health Commissioning - Coleman, Mathew; Cuesta-Briand, Beatriz; Collins, Noel (Frontiers in Psychiatry, 2022)
The prevalence of mental illness is a critical public health issue. In Australia, the prevalence of mental illness is similar across all settings, however, people living in rural and remote areas experience worse outcomes than their urban counterparts. Access to mental health services is critical, however, the notion of accessibility needs to be understood in the context of the uniqueness and variability of the rural experience. The Orange Declaration on Rural and Remote Mental Health recognised that rural areas face a series of interconnected challenges and called for place-specific responses and new funding models that reward collaboration and local partnerships. In this paper, we argue that recent mental health planning, policy and service development uses a narrow interpretation of the notion of accessibility that is out of step with current thinking on the heterogeneity of the rural experience. We use some examples of our own research and experience in rural Western Australia to argue that the current commissioning model is not aligned with the Orange Declaration, and remains largely metro-centric and reliant on a narrow conceptualisation of service accessibility. We argue that what is needed is a dynamic, responsive, context-sensitive understanding of accessibility that is informed by the distinctiveness of rural adversity, and recognises the heterogeneity and variability of the rural experience whilst acknowledging rural agency and social capital, and we suggest that applying a socio-ecological approach to the development of new commissioning models provides a way forward.